2021
DOI: 10.1101/2021.02.10.430545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fasting reverses drug-resistance in hepatocellular carcinoma through p53-dependent metabolic synergism

Abstract: Cancer cells voraciously consume nutrients to support their growth, exposing a metabolic vulnerability that can be therapeutically exploited. Here we show in hepatocellular carcinoma (HCC) cells, xenografts, and in patient-derived HCC organoids that fasting can synergistically sensitize resistant HCC to sorafenib. Mechanistically, sorafenib acts non-canonically as an inhibitor of mitochondrial respiration, causing resistant cells to depend on glycolysis for survival. Fasting, through reduction in glucose and i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 93 publications
1
6
0
Order By: Relevance
“…Recent reports showed that p53 protein abundance is increased in cultured hepatocytes by starvation [28] and that p53 signaling is necessary for the physiological response to fasting in the mouse liver [28,30]. Furthermore, our most recent data provide evidence for the requirement of p53 for the effects of fasting in enhancing hepatocellular carcinoma therapy (Preprint at BioRxiv [29]). Thus, our ndings add to a ourish of recent reports that establish p53 as central and potent metabolic regulator in transformed as well as in nontransformed cells [49,65].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Recent reports showed that p53 protein abundance is increased in cultured hepatocytes by starvation [28] and that p53 signaling is necessary for the physiological response to fasting in the mouse liver [28,30]. Furthermore, our most recent data provide evidence for the requirement of p53 for the effects of fasting in enhancing hepatocellular carcinoma therapy (Preprint at BioRxiv [29]). Thus, our ndings add to a ourish of recent reports that establish p53 as central and potent metabolic regulator in transformed as well as in nontransformed cells [49,65].…”
Section: Discussionsupporting
confidence: 52%
“…and that p53 is necessary and su cient for the therapy-enhancing effect of fasting on sorafenib treatment of hepatocellular carcinoma (Preprint at BioRxiv [29]). Moreover, hepatic p53 was recently shown to be stabilized by O-GlcNAcylation in fasted mice, which was shown to be essential for the regulation of gluconeogenesis in the liver [30].…”
Section: Introductionmentioning
confidence: 99%
“…HepG2 cells (ATCC) were cultivated in Dulbecco’s modified Eagle’s medium with 25 mM of glucose, supplemented with 4 mM glutamine, 10% FBS, and 500 U/ml penicillin-streptomycin (GIBCO) as previously ( 52 ). Glycogen was quantified using a kit (K646-100, BioVision).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, IF can reverse MDR by several pathways as revealed in the literature. The first way is by increasing p53, which is substantial for sensitization (47). By the same token, IF suppresses IGF-1 and IGF-1 receptors and that increases sensitivity to chemotherapy (48) The safety profile of anticancer agents is crucial to evaluating their toxicity.…”
Section: Discussionmentioning
confidence: 99%